PENERAPAN TEKNOLOGI PAKAN SILASE RUMPUT GAJAH UNTUK MENDUKUNG MANAJEMEN PAKAN TERNAK PADA MUSIM KEMARAU - Koji Al Adam; Nuraida; Nanda Fatmala; Muhammad Haris Muttaqim; Baihaqi; Diah Fridayati (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
The problem experienced by cattle farmers in this community service activity is that it is difficult to provide green fodder for ruminant livestock during the dry season. This community service activity aimed to increase students' knowledge and skills in making silage for ruminant livestock feed. This silage feed technology application program involved lecturers, students, and farmer groups through the methods: 1) pre-test, 2) socialization, 3) training with direct demonstrations, 4) feed application simulation, 5) conducting evaluations, and 6) post-test. The results of this activity showed that all livestock group participants were able to produce high quality silage to support animal feed management. Apart from that, the group also gave a good response in understanding the material provided with an increase in the average score of the post-test given. So it was concluded that the farmer group was able to make silage continuously and independently by choosing quality and easy to obtain materials.